Analisis kinerja MIT AI2 Penerjemahan Bahasa - Ana Rahayu; Dela Putri Jaya Nisrina Nisrina (Journal of Information Systems and Business Technology, 2025)
This research aims to analyze the performance and potential of an android-based application developed with MIT App Inventor 2 (AI2), specifically focusing on the MIT AI2 Translator for language traslator. The primary abjective is to explore the effectiveness of MIT App Inventor 2 (AI2) for language translator applications.The study involves two main stages:designing the learning application using MIT AI2 software and conducting usability testing of the application. In the first stage, the researcher designed a language translator application using MIT AI2. The second stage involves testing the application’s usability to determine its quality. Translator features were integrated using visual programming blocks provided by MIT AI2. This research utilized four language: Java, English, Jaoabese dan italy. The findings indicate that the research successfully created android-based language translator using MIT AI 2.